Group motion in practice : collective creation through dance movement improvisation - Herrmann, Brigitta (McFarland & Company, Inc., Publishers, 2018)
"Part memoir, part guidebook, part philosophy of art treatise, this book provides step-by-step guidance to dozens of improvisational structures or games for dance professionals, theater artists, musicians and other performers who use movement for creative expression"--